A compliant aortic model for in vitro simulations: Design and manufacturing process. (September 2018) - Marconi, Stefania; Lanzarone, Ettore; van Bogerijen, Guido H.W.; Conti, Michele; Secchi, Francesco; Trimarchi, Santi; Auricchio, Ferdinando
Highlights: A compliant silicone model of the entire human aorta is proposed. The model mimics both geometrical and mechanical local properties of the aorta. It can be used as a customizable tool for the in vitro testing of vascular devices. Graphical abstract: Abstract: We design and manufacture a silicone model of the human aorta, able to mimic both the geometrical and the mechanical properties of physiological individuals, with a specific focus on reproducing the compliance. In fact, while the models available in the literature exhibit an unrealistic compliant behavior, though they are detailed from the geometrical viewpoint, here the goal is to provide an accurate compliant tool for in vitro testing the devices that interface with the vascular system. A parametric design of the aortic model is obtained based on the available literature data, and the model is manufactured with a specific silicone mixture using rapid prototyping and molding techniques. The manufactured prototype has been tested by means of computed tomography scans for evaluating the matching of the mechanical properties with the desired ones. Results show a high degree of adherence between the imposed and the measured compliance values for each main aortic section. Thus, our work proves the feasibility of the approach, and the possibility to manufacture compliant models that reproduce the mechanical behavior of the aorta for in vitro studies.